(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine disorder affecting women of reproductive age. Characterized by hormonal imbalances, irregular ovulation, and metabolic disturbances, PCOS is not only a reproductive disorder but also a significant risk factor for cardiovascular disease (CVD) and type 2 diabetes. This article examines the metabolic consequences of PCOS, including insulin resistance, dyslipidemia, obesity, and hypertension, and discusses current and emerging therapeutic strategies.